The effect of magnetic and electromagnetic fields on the morpho-anatomical characteristics of corn (Zea mays l.) during biomass production (2016)
There are several sources of raw material that have been identified worldwide with some potential to be used for the production of biofuels; for this reason hard work has been put into increasing the yields per unit area and increasing the sugar content (as in the case of corn). There are only a small number of studies that have analyzed the morpho-anatomical behaviour of crops modified for biomass production. For this reason, this work studied the morpho-anatomical, developmental and physiochemical changes in Zea mays L. plants when exposed to magnetic and electromagnetic fields with a view to the large-scale production of biomass for the generation of biofuels. Seeds were exposed to different fields for 21 days, with a control group of seeds that were not exposed. Sowing was carried out in 100 cm3 trays using coconut fiber as a substrate. The substrate had been disinfected and moistened prior to use. The sowing trays were placed in a semi-controlled growth chamber at a light intensity of 3,000 lux, with light cycles of 12 hours and at a temperature of 23°C. The variables studied were the growth dynamics of coleoptiles and plants, the complete bromatological analysis and the anatomical structure. The bromatological analysis included the percentage variation of dry matter, crude protein, ether extract, ash content, organic matter, crude fibre, neutral detergent fibre (NDF), acid detergent fibre (ADF) and calcium, lignin and water activity. The anatomical structure was studied to identify relevant histological changes and mainly focused on the arrangement of parenchymatous tissue and the shape of the cells of which it is comprised. In addition, evaluations were conducted regarding the development of the crop based on the following indicators: relative growth rate, net assimilation rate, leaf area index, crop growth rate, absolute growth rate, leaf area duration and specific leaf area. The best results were obtained on plants whose seeds were treated with electromagnetic fields. A significant increase was seen in the majority of the indicators studied. This was most evident in the development of the parenchymal tissue and thus the chlorophyll content, as was clearly seen in the histological sections. It is important to emphasize that the histological technique allowed us to identify areas of the greatest concentrations of chlorophyll (shown by differing shades of green) in plants whose seeds had been subjected to electromagnetic fields. An increase in the chlorophyll level gives us an indirect measure of the high potential these plants offer for producing biomass.